Purification to homogeneity and partial characterization of interleukin 2 from a human T-cell leukemia. - Stern, A S (1984)
A method utilizing reversed-phase high-performance liquid chromatography has been developed for the purification to homogeneity of interleukin 2 (IL-2) isolated from a human T-cell leukemia. A final purification of 500,000-fold was obtained with a specific activity of pure IL-2 of 10(9) units/mg. The amino acid analysis of natural IL-2 is strikingly similar to the composition deduced from sequence analysis of a cDNA coding for human IL-2. Protein sequence analysis of CNBr-derived peptides yields data consistent with the sequence proposed from cloned cDNA. The availability of homogeneous IL-2 will allow accurate biological studies of its activity free from the contamination of the numerous lymphokine species that are known to be co-produced with IL-2 during the induction procedure.